Multi-color tunable circularly polarized luminescence in one single AIE system. Issue 8 (22nd January 2020) - Shang, Hongxing; Ding, Zeyang; Shen, Yue; Yang, Bing; Liu, Minghua; Jiang, Shimei
Abstract : A multi-color tunable circularly polarized luminescence (CPL) xerogel film with a large luminescence dissymmetry factor ( g lum ) is achieved using a single compound upon protonation. Abstract : Circularly polarized luminescence (CPL) materials with a large luminescence dissymmetry factor ( g lum ) and multi-color properties are very attractive. While multi-color tunable CPL can be realized by different organic dyes, the challenge of realizing both a higher g lum and multiple colors using a single component remains. Here, we design an aggregation-induced emission (AIE) fluorophore, which is a pyridine functionalized cyanostilbene attached to a chiral unit, and realize multi-color tunable CPL with a high g lum . The compound can self-assemble into a nanohelix and form both gel and xerogel films, exhibiting blue CPL with large g lum values of −3.0 × 10 −2 and −1.7 × 10 −2, respectively. With the assistance of pyridine protonation, the xerogel films exhibit red-shifted CPL signals from 480 nm to 530 nm, covering from blue via green and yellow to orange. Additionally, the g lum remains constant during the process. This work paves a simple and convenient way to construct multi-color tunable CPL materials using a single molecule.